Oxytocin-induced prostaglandin F2-alpha release is low in early bovine pregnancy but increases during the second month of pregnancy. Issue 2 (2nd September 2019) - Drum, Jéssica N; Wiltbank, Milo C; Monteiro, Pedro L J; Prata, Alexandre B; Gennari, Rodrigo S; Gamarra, Caio A; Canavessi, Aurea M O; Sartori, Roberto
Abstract: Circulating prostaglandin F2α metabolite (PGFM) after an oxytocin challenge was evaluated throughout the first 2 months of pregnancy in lactating Holstein cows. On day 11, 18, and 25 after artificial insemination (AI), and on days 32, 39, 46, 53, and 60 of pregnancy, cows were challenged with 50 IU oxytocin, i.m. Blood was collected before (0 min), 30, 60, 90, and 120 min after oxytocin for plasma PGFM concentrations. Ultrasound evaluations were performed for pregnancy diagnosis on day 32–60 post-AI. Nonpregnant (NP) cows on day 18 were designated by a lack of interferon-stimulated genes in peripheral blood leukocytes and Pregnant (P) based on day 32 ultrasound. On day 11, P and NP were similar with low PGFM and no effect of oxytocin on PGFM. On day 18, oxytocin increased PGFM (3-fold) in NP with little change in P cows. Comparing only P cows from day 11 to 60, basal circulating PGFM increased as pregnancy progressed, with day 11 and 18, lower than all days from day 25 to 60 of pregnancy. Oxytocin-induced PGFM in P cows on day 25 was greater than P cows on day 18 (2.9-fold). However, oxytocin-induced PGFM was lower on day 25 compared to day 53 and 60, with intermediate values on day 32, 39, and 46 of pregnancy. Thus, the corpus luteum (CL) of early pregnancy (day 11, 18) is maintained by suppression of PGF, as reflected by suppressed PGFM in this study. However, during the second month of pregnancy, uterine PGF secretion was not suppressed since basal PGFM and oxytocin-induced PGFM secretion were elevated. Apparently, mechanisms other than suppression of oxytocin receptors maintain CL after day 25 of pregnancy. Abstract : Summary sentence : On day 18 of pregnancy, there is suppressed PGF production in response to oxytocin; however, at day 25–60 of pregnancy, there is increased basal PGF and increased oxytocin-induced PGF indicating the presence of oxytocin receptors and different mechanisms maintaining CL of pregnancy after day 25.